Circulating gonadal and adrenal steroids in amyotrophic lateral sclerosis: possible markers of susceptibility and outcome - Gargiulo Monachelli, Gisella Mariana (2014)
Although changes of circulating steroids have been reported in patients with sporadic amyotrophic lateral sclerosis (ALS), a full comparison of the adrenal and gonadal steroid profile between control subjects and ALS patients is lacking. Considering that respiratory failure is the most frequent cause of death in ALS, we looked into whether a relationship emerged between circulating steroids and respiratory parameters. Serum levels of adrenal and gonadal steroids were measured in 52 age- and gender-matched subjects (28 ALS and 24 controls) using radioimmunoassay techniques. We also evaluated respiratory parameters in ALS patients, including forced vital capacity (FVC), maximal inspiratory pressure (MIP), and maximal expiratory pressure (MEP). We found increased levels of testosterone in female ALS patients compared to healthy female subjects. Furthermore, control subjects showed a significant decline of testosterone, dehydroepiandrosterone and its sulfate, and a borderline decline of progesterone with increasing age. Instead, testosterone did not decline with increasing age in ALS patients. We also found that the dehydroepiandrosterone sulfate/cortisol ratio was positively associated with FVC, MIP, and MEP. Moreover, ALS patients showing higher testosterone levels and lower progesterone/free testosterone ratio presented a more rapid worsening of the monthly FVC. In conclusion, first our study revealed a differential steroid profile with age and gender in ALS patients relative to controls. Second, we demonstrated an association between some steroids and their ratios with respiratory function and disease progression. Thus, we hypothesize that the endogenous steroid profile could be a marker of susceptibility and prognosis in ALS patients.